If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2x + 3) = 81 Reorder the terms: 9(3 + 2x) = 81 (3 * 9 + 2x * 9) = 81 (27 + 18x) = 81 Solving 27 + 18x = 81 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 18x = 81 + -27 Combine like terms: 27 + -27 = 0 0 + 18x = 81 + -27 18x = 81 + -27 Combine like terms: 81 + -27 = 54 18x = 54 Divide each side by '18'. x = 3 Simplifying x = 3
| x^2-11x-38=-3x-5 | | 2(4x+2)=3 | | x^2+7x-12=6 | | 6(2g+8)=8 | | 6(2g+8)= | | 99-3x=24x+15 | | 37-v=-8(-v-8) | | 5-10x=43-17x | | -8p=4-4p | | 3x+12=-48-7x | | -8p=42-42p | | x^2+3x=45 | | 5x+4=39 | | x^2+3x=45x | | 3x^6+6x^5-9x^4+6x^3=0 | | 5x+4=41 | | 8x+10=12x-90 | | 24x-50=4x-20 | | 9(4x+1)= | | -7a+50=-6-7(6+3a) | | 20x+30=10x+90 | | x^3+14x^2+49x=0 | | 2x+51.5=4x+3 | | 8(1-p)=-24-4p | | x^3-15=0 | | y=0.2192x+15.29 | | 100+14r= | | 0.2192x+15.29= | | 2x+4/3+54= | | R=100 | | 5(4x-6)-3x=47+6x | | 2+8+9+6-87-654-9+87654= |